THE NEED ANALYSIS OF MATERIAL DESIGN IN ENGLISH TEACHING ON ESP PROGRAM - Ida Maulida (Media Bina Ilmiah, 2024)
Material design for learning English is important for use of students. It is referring to students' needs and interests in ESP classroom. To achieve this goal, ESP teachers organize the material completely by Needs Analysis. Needs analysis determines the language and skills learners require to complete their studies. In this are focus on target need (what the learner needs to do in the order to learn) and learning needs (what the learners need to do in order to learn). The purpose of this research was to determine the role Needs Analysis in curriculum and design material on ESP classroom. This study used a qualitative descriptive. The total in the research 89 participants randomly selected from the total sample population were surveyed about their views regarding the ESP classroom program through questionnaire. Based on responses to questionnaires regarding students' perceptions of learning English in ESP classes, the majority of the students implied to be comfortable accomplishing the course. In needs analysis, students most often choose more representative English language learning meet the need for language skills in the field that result on Strong Agree (SA) 60 is 67,42%, Agree (A) 12 students is 13,48%, Undecided (U) 17 is 19,10%. Meanwhile, respond to need English materials for casual environment/daily conversation with colleagues a small answer was given Strong Agree (SA) 8 is 8,99%, Agree (A) 64 students is 71,91%, Undecided (U) 17 is 19,10%. The outcomes demonstrate the importance of ESP learning, particularly in English material, which is more representative of students.